Fate of Pyrrolizidine Alkaloids in Soil: Insights from Myosotis arvensis L. and Senecio vulgaris L. - Ilva Nakurte; Gundars Skudriņš; Ieva Mežaka (Toxins, 2025)
Pyrrolizidine alkaloids are plant-derived toxins with environmental persistence and the potential to contaminate soil, water, and adjacent crops. This study investigated the leaching behavior and environmental fate of PAs from two PA-producing weeds—Myosotis arvensis L. (Boraginaceae) and Senecio vulgaris L. (Asteraceae)—in two Latvian agricultural soils: sandy loam and loam. Hot- and cold-water plant extracts were applied to soil columns (10 cm and 20 cm), and leachates were analyzed over a 14-day period using QuEChERS purification and LC-HRMS detection. Leaching varied by plant species, extract type, and soil. M. arvensis showed significantly higher cumulative leaching (77–84% for cold, 65–71% for hot extracts), attributed to the higher solubility of N-oxides. In contrast, S. vulgaris extracts leached minimally (<0.84% from sandy loam) and were undetectable in loam. The presence of cyclic diester PAs in S. vulgaris and the higher cation exchange capacity of loam favored retention or degradation. PANO-to-PA conversion occurred in both soils, indicating redox activity. The fate of PAs was influenced by structural type (diesters showing higher persistence), extraction method (hot extraction releasing more pyrrolizidine alkaloids), and soil properties such as pH, organic matter, and cation exchange capacity, which affected sorption and mobility. These findings underscore the significance of soil composition in controlling PA mobility and associated environmental risks. Future research should focus on long-term PA persistence across diverse soil types and investigate crop uptake potential and microbial degradation pathways under field conditions.